2007
DOI: 10.1086/518595
|View full text |Cite
|
Sign up to set email alerts
|

Production Pathways of CCS and CCCS Inferred from Their13C Isotopic Species

Abstract: The rotational spectral lines (J N ¼ 3 2 Y2 1 and J N ¼ 2 1 Y1 0 ) of 13 CCS and C 13 CS have been observed toward a cold dark cloud, TMC-1. The strongest hyperfine component lines of 13 CCS and C 13 CS (J N ¼ 2 1 Y1 0 , F ¼ 5/2Y3/2) have successfully been detected. The C 13 CS ½ / 13 CCS ½ abundance ratio is determined to be 4:2 AE 2:3 (3 ). The CCS ½ / 13 CCS ½ ratio is evaluated to be 230 AE 130 (3 ), and hence, 13 CCS is found to be significantly diluted. Such a difference between the 13 CCS and C 13 CS ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 28 publications
6
67
0
Order By: Relevance
“…We recently reported on the abundance anomaly of the 13 C species of CCS in the young starless cores TMC-1 and L1521E (Sakai et al 2007a). The abundance ratio of [CCS]/[C 13 CS] in TMC-1 is determined to be 54 ± 5 (3σ), which is almost consistent with the interstellar [ 12 C]/[ 13 C] ratio of 60 (Lucas & Liszt 1998).…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…We recently reported on the abundance anomaly of the 13 C species of CCS in the young starless cores TMC-1 and L1521E (Sakai et al 2007a). The abundance ratio of [CCS]/[C 13 CS] in TMC-1 is determined to be 54 ± 5 (3σ), which is almost consistent with the interstellar [ 12 C]/[ 13 C] ratio of 60 (Lucas & Liszt 1998).…”
Section: Introductionsupporting
confidence: 54%
“…Although we made a more detailed integration for 13 CCH than for C 13 CH toward L1527 to improve the S/N ratio, we confirmed that the line intensities of 13 CCH observed simultaneously with the C 13 CH lines are consistent with those finally obtained after the extended observation. Hence it is clearly established that the abundances of the two 13 C isotopic species are different, as in the case of HC 3 N (Takano et al 1998) and CCS (Sakai et al 2007a). Since the H 2 densities of TMC-1 and L1527 are ∼3×10 4 (Sect.…”
Section: Abundance Anomaly Of the 13 C Species Of Cchmentioning
confidence: 95%
See 2 more Smart Citations
“…While ammonia was the first polyatomic molecule to be discovered in the interstellar medium (review e.g. by Ho & Townes 1983), the CCS radical was first identified far more recently (Saito et al 1987) and the main pathways leading to its formation remain a subject of discussion (Suzuki et al 1992;Petrie 1996;Sakai et al 2007), although it is frequently observed along with other carbon-chain molecules (e.g., Hirota et al 2009).…”
Section: Introductionmentioning
confidence: 99%